2021
DOI: 10.1016/j.aca.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium(II) complex-based probe for colorimetric and luminescent detection and imaging of hydrogen sulfide in living cells and organisms

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The metabolites of H 2 S, such as polysulfides and persulfides, are also important RSS that may have similar or divergent regulatory roles in living systems [ 206 , 207 ]. Recently, by exploiting the response mechanisms of sulfoxide reduction [ 194 ], displacement of Cu 2+ [ 137 ], cleavage of 7-nitro-2,1,3-benzoxadiazoles (NBD) [ 208 ] and DNP [ 209 ], a few Ru(II) complexes have been developed as chemosensors for RSS detection [ 194 ], and these RSS-responsive Ru(II) complexes will be discussed in this section.…”
Section: Ru(ii) Complex Chemosensors For Reactive Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites of H 2 S, such as polysulfides and persulfides, are also important RSS that may have similar or divergent regulatory roles in living systems [ 206 , 207 ]. Recently, by exploiting the response mechanisms of sulfoxide reduction [ 194 ], displacement of Cu 2+ [ 137 ], cleavage of 7-nitro-2,1,3-benzoxadiazoles (NBD) [ 208 ] and DNP [ 209 ], a few Ru(II) complexes have been developed as chemosensors for RSS detection [ 194 ], and these RSS-responsive Ru(II) complexes will be discussed in this section.…”
Section: Ru(ii) Complex Chemosensors For Reactive Biomoleculesmentioning
confidence: 99%
“…By exploiting the H 2 S-triggered thiolysis of NBD, Ru(II) complex 51 was recently developed by Liu et al for the detection of H 2 S in PBS buffer and in living organisms (Fig. 24 B) [ 208 ]. Similar to complex 50 , the emission quenching of complex 51 was attributed to the PeT from the Ru(II) center to DNB.…”
Section: Ru(ii) Complex Chemosensors For Reactive Biomoleculesmentioning
confidence: 99%
“…The metabolites of H 2 S, such as polysulfides and persulfides, are also important RSS that may have similar or divergent regulatory roles in living systems [206,207]. Recently, by exploiting the response mechanisms of sulfoxide reduction [194], displacement of Cu 2+ [137], cleavage of 7-nitro-2,1,3-benzoxadiazoles (NBD) [208] and DNP [209], a few Ru(II) complexes have been developed as chemosensors for RSS detection [194], and these RSS-responsive Ru(II) complexes will be discussed in this section.…”
Section: Ru(ii) Complex Chemosensors For Rssmentioning
confidence: 99%
“…By exploiting the H 2 S-triggered thiolysis of NBD, Ru(II) complex 51 was recently developed by Liu et al for the detection of H 2 S in PBS buffer and in living organisms (Fig. 24B) [208]. Similar to complex 50, the emission quenching of complex 51 was attributed to the PeT from the Ru(II) center to DNB.…”
Section: Ru(ii) Complex Chemosensors For Rssmentioning
confidence: 99%
“…Liu et al [ 80 ] reported a ruthenium (Ru) (II) complex-based probe for colorimetric and luminescent detection and imaging of H 2 S in live cells and organisms. This Ru(II) complex was yellow color and nonluminescent in aqueous solution.…”
Section: Dual-mode Detection For Live Cell Analysismentioning
confidence: 99%